ULTRASOUND DIAGNOSTICS OF POSTPARTUM ENDOMETRITIS - Nazarova Z.Yu.; Saidova Dilnoza Jalolovna (World Scientific Research Journal, 2025)
Resume. The data on the diagnosis of postpartum infections in women with chronic endometritis, which occurs against the background of the use of intrauterine devices and without the use of intrauterine devices, are presented. High levels of cytokines were found in women in both groups, and an immunomodulator was used for modern treatment.